The impact of re‐transurethral resection on clinical outcomes in a large multicentre cohort of patients with T1 high‐grade/Grade 3 bladder cancer treated with bacille Calmette–Guérin. (6th November 2015) - Gontero, Paolo; Sylvester, Richard; Pisano, Francesca; Joniau, Steven; Oderda, Marco; Serretta, Vincenzo; Larré, Stéphane; Di Stasi, Savino; Van Rhijn, Bas; Witjes, Alfred J.; Grotenhuis, Anne J.; Colombo, Renzo; et al.
Abstract : Objectives: To determine if a re‐transurethral resection (TUR), in the presence or absence of muscle at the first TUR in patients with T1‐high grade (HG)/Grade 3 (G3) bladder cancer, makes a difference in recurrence, progression, cancer specific (CSS) and overall survival (OS). Patients and methods: In a large retrospective multicentre cohort of 2451 patients with T1‐HG/G3 initially treated with bacille Calmette–Guérin, 935 (38%) had a re‐TUR. According to the presence or absence of muscle in the specimen of the primary TUR, patients were divided in four groups: group 1 (no muscle, no re‐TUR), group 2 (no muscle, re‐TUR), group 3 (muscle, no re‐TUR) and group 4 (muscle, re‐TUR). Clinical outcomes were compared across the four groups. Results: Re‐TUR had a positive impact on recurrence, progression, CSS and OS only if muscle was not present in the primary TUR specimen. Adjusting for the most important prognostic factors, re‐TUR in the absence of muscle had a borderline significant effect on time to recurrence [hazard ratio (HR) 0.67, P = 0.08], progression (HR 0.46, P = 0.06), CSS (HR 0.31, P = 0.07) and OS (HR 0.48, P = 0.05). Re‐TUR in the presence of muscle in the primary TUR specimen did not improve the outcome for any of the endpoints. Conclusions: Our retrospective analysis suggests that re‐TUR may not be necessary in patients with T1‐HG/G3, if muscle is present in the specimen of the primary TUR.